2006
DOI: 10.1902/jop.2006.050125
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Variables Affecting Patient Referrals From General Practice Dentists to Periodontists

Abstract: This study indicates that four demographic variables have a statistical influence on the number of referrals per month from a GP to a periodontist. These variables are as follows: female gender, practicing with one other dentist, employing two or more hygienists, and being >5 miles away from the nearest periodontist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
75
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(86 citation statements)
references
References 8 publications
9
75
1
Order By: Relevance
“…This approach involves specific behaviors on the part of endodontists that increase opportunities to interact with GPs and facilitate the perception that the GPs are teammates whose input and needs are valued by endodontists. These results concur with past research on other specialist referrals where communication was identified as a key factor in the referral decision (7,12,13). The listed behaviors might be subject to the moderating effects of gender (female GPs) and years in practice (GPs in practice 6-10 years).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This approach involves specific behaviors on the part of endodontists that increase opportunities to interact with GPs and facilitate the perception that the GPs are teammates whose input and needs are valued by endodontists. These results concur with past research on other specialist referrals where communication was identified as a key factor in the referral decision (7,12,13). The listed behaviors might be subject to the moderating effects of gender (female GPs) and years in practice (GPs in practice 6-10 years).…”
Section: Discussionsupporting
confidence: 89%
“…A wider-reaching study is needed to further investigate these effects as well as to identify other demographic variables that might impact efforts to attract referral business. The effects of gender (7,14) and years in practice/clinical experience (5) in GP referral patterns have been noted in the past.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that various factors such as gender of the dentist and the proximity to a periodontist affected the number of referrals by a general dentist. [5] Also, treatment of chronic periodontal disease was the most common periodontal procedure that was referred, followed by soft tissue grafting procedures, and implants. A comprehensive demographic study in the United States was authorized by the American Academy of Periodontology (AAP) in 1981.…”
Section: Introductionmentioning
confidence: 99%
“…Today, it is accepted that both oral surgeons and periodontists are capable of placing implants. Cottrell et al (10) found that 31.0% of general dentists refer patients to periodontists for implant placement, and Zemanovich et al (17) found that 51.9% of general dentists reported the same. Perhaps the respondents who reported that other specialists would support endodontists placing implants believe that general dentists and specialists would eventually recognize the value of having multiple specialists being able to provide implant placement for patients, especially if endodontic residency programs were modified to incorporate the additional training required to place implants.…”
Section: Discussionmentioning
confidence: 99%